(untitled) (Physical Education, Health and Social Sciences, 2026)
In underdeveloped countries such as Pakistan, where resources and medical support are limited and the burden of the disease is high, tuberculosis (TB) is a serious public health phenomenon that is not only difficult to diagnose but to treat. Particularly in those instances where sophisticated molecular testing such as GeneXpert is not widely available, chest radiography (CXR) remains an important diagnostic method for the early diagnosis of pulmonary TB. The purpose of this study was to assess the awareness of healthcare personnel for the role that chest radiography plays in TB diagnosis at tertiary care facilities of Peshawar. A standardized questionnaire was used to make a cross-sectional survey with the 80 healthcare professionals, while the analysis was made with the help of the Statistical package for social sciences (SPSS). Regarding the findings of this study, most of the subjects acknowledged chest radiography as an important and additional method of TB diagnosis, as well as the fact that chest radiography is useful in recognizing early cases even before clinical symptoms have fully developed. Nonetheless, knowledge gaps were pointed out, particularly in relation to CXR integration with other diagnostic modalities and the reading of the radiographic results. IN order to help healthcare personnel, gain more proficiency in diagnosing infectious disease, the need for continual training programs and awareness activities is highlighted in this study. Improving the role of chest radiography in TB diagnosis can significantly affect the early diagnosis of cases, initiate treatment and ultimately, but by no means immediately, disease control at the local and the national level. The study concludes: Healthcare professionals of Peshawar demonstrate strong awareness and positive attitudes towards the use of CXR in TB detection but its little utilization and systemic issues restrain its utilization potential. Strengthening well into training programmes, improving quality images and better incorporation of radiography in a more systemic way into national TB control (enhancing diagnosis early and reducing the burden of the disease) is recommended. However, the full potential of its use is limited due to underutilization and systemic barriers. The report suggests enhancing training programs, enhancing image quality, and making sure radiography is systematically incorporated into national TB control plans in order to optimize its efficacy. This will help with early diagnosis and lower the overall disease burden.